Life mode of in situ Conularia in a Middle Devonian epibole - Van Iten, Heyo; Tollerton, Victor P.; Ver Straeten, Charles A.; De Moraes Leme, Juliana; Simões, Marcello Guimarães [UNESP]; Rodrigues, Sabrina Coelho (Wiley, 2013)
Exceptionally abundant specimens of Conularia aff. desiderata Hall occur in multiple marine obrution deposits, in a single sixth-order parasequence composed of argillaceous and silty very fine sandstone, in the Otsego Member of the Mount Marion Formation (Middle Devonian, Givetian) in eastern New York State, USA. Associated fossils consist mostly of rhynchonelliform brachiopods but also include bivalve molluscs, orthoconic nautiloids, linguliform brachiopods and gastropods. Many of the brachiopods, bivalve molluscs and conulariids have been buried in situ. Conulariids buried in situ are oriented with their aperture facing obliquely upward and with their long axis inclined at up to 87degree to bedding. Most specimens are solitary, but some occur in V-like pairs or in radial clusters consisting of three specimens, with the component specimens being about equally long or (less frequently) substantially different in length. The compacted apical end of Conularia buried in situ generally rests upon argillaceous sandstone. With one possible exception, none of the examined specimens terminates in a schott (apical wall), and internal schotts appear to be absent. The apical ends of specimens in V-like pairs and radial clusters show no direct evidence of interconnection of their periderms. The apical, middle or apertural region of some inclined specimens abuts or is in close lateral proximity to a recumbent conulariid or to one or more spiriferid brachiopods, some of which have been buried in their original life orientation. The azimuthal bearings of Conularia and nautiloid long axes and the directions in which conulariids open are nonrandom, with conulariids being preferentially aligned between 350 and 50degree and with their apertural end facing north-east, and nautiloids being preferentially aligned between 30 and 70degree. Otsego Member Conularia were erect or semi-erect, epifaunal or partially infaunal animals, the apical end of which rested upon very fine bottom sediment. The origin of V-like pairs and radial clusters remains enigmatic, but it is probable that production of schotts was not a regular feature of this animal's life history. Finally, conulariids and associated fauna were occasionally smothered by distal storm deposits, under the influence of relatively weak bottom currents. © The Palaeontological Association.
Keywords: Conulariids; Ecological epibole; Life mode; Middle Devonian; Mount Marion Formation; Obrution deposits; bivalve; brachiopod; Devonian; epifauna; fossil; jellyfish; paleontology; parasequence; New York [United States]; United States; Animalia; Bivalvia; Brachiopoda; Conulariida; Gastropoda; Mollusca; Nautilida; Spiriferida